Persepsi Orang Tua Terhadap Profesi Petani Bagi Anak-anaknya - Luthfiana, Hanifa Aulia; Prayoga, Kadhung; Gayatri, Siwi (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
The background of this research is farmer regeneration that decreasing over time, parents are reluctant to pass on the profession of farming which is synonymous with poverty, low social status and dirtiness to their children which are feared to affect farmers’ perceptions of the farmers profession for their children in Ngunut Village, Babadan District, Ponorogo Regency.This research was conducted with the aim of: 1) analyze parents' perception of farmers profession for their children; 2) analyze the factors that influence the perception of parents' toward profession of farmers for their children in Ngunut Village. This research was condicted in June – July 2023 in Ngunut Village, Babadan District, Ponorogo Regency. The research method used was a survey method with purposive sampling of 54 farmers. The analytical methods used are descriptive analysis and multiple linear regression analysis. The results showed that farmers’ perceptions of the farmers profession for their children obtained an average score of 2.451 with an index score of 64,8%, which means it is included in the good category. Variable farmer age, farmer education level, length of farming, farming income for 1 period, and land area simultaneously affect farmers’ perceptions of the farmers profession for their children, while partially only length of farming and land area variables affect farmers’ perceptions of the farmers profession for their children. It is hoped that this research can be used as material for consideration that parents' perception of the farmers profession is quite good, it is hoped that parents will be willing to support their children to continue their parents' farming business and develop it to higher productivity.